ELDERLY BEHAVIOR SETTING TO RESPONDING ERUPTION DISASTER AT THE TRESNA WERDHA SOCIAL SERVICE CENTER, PAKEMBINANGUN - Kristiadi, Adimas; Sabatini, Stefani Natalia (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2025)
The purpose of this study is to investigate how the elderly respond to disaster situations involving volcanic eruptions in Indonesia. The study was conducted at the Tresna Werdha Social Service Center (Balai Pelayanan Sosial Tresna Werdha—BPSTW) in Pakembinangun, located 14 km from the summit of Mount Merapi, the most active volcano in Indonesia. This research applied an in-depth analysis of the behavior settings of vulnerable elderly groups using a deductive-qualitative research method. The data collection methods included observation, behavior mapping, time budgeting, and interviews. The research results include the formulation of standard behavior patterns of the elderly in responding to the potential for volcanic eruptions, particularly at BPSTW: 1) Comfort and safety are obtained from rooms/lodgings that have high accessibility and visibility (close to exits and close to assembly areas); 2) Elderly individuals with total physical disabilities and severe mental impairments require assistance for emergency response activities, necessitating quick connectivity in terms of accessibility and visibility for caregivers and other elderly individuals (mutual assistance); 3) Agreement on the division of roles and responsibilities between managers and the elderly in emergency response activities (formation of an emergency response team; regular disaster mitigation training). These behavioral settings can contribute to the basic knowledge of inclusive design, particularly for vulnerable elderly groups in responding to specific conditions related to volcanic eruption disasters.